2016
DOI: 10.1002/aoc.3604
|View full text |Cite
|
Sign up to set email alerts
|

Copper immobilized onto polymer‐coated magnetic nanoparticles as recoverable catalyst for ‘click’ reaction

Abstract: Copper supported on polymer-coated magnetic nanoparticles was designed and synthesized as a separable heterogeneous catalyst. The catalyst was fully characterized using several techniques such as Fourier transform infrared and energy-dispersive X-ray spectroscopies, scanning and transmission electron microscopies, X-ray diffraction, vibrating sample magnetometry, thermogravimetric analysis and inductively coupled plasma atomic emission spectrometry. All results showed that copper was successfully supported on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Several polymer-coated MNPs have been designed and used to support the immobilization of copper salts over the last few decades. Valizadeh et al reported that MNPs functionalized with poly(4-vinylpyridine) immobilized copper(II) salts [150]. This material was used as a recoverable heterogeneous catalyst for a one-pot synthesis of 1,4-triazoles from terminal alkynes, alkyl halides, and sodium azide.…”
Section: Magnetic Solid-supported Catalysts For Cuaacmentioning
confidence: 99%
“…Several polymer-coated MNPs have been designed and used to support the immobilization of copper salts over the last few decades. Valizadeh et al reported that MNPs functionalized with poly(4-vinylpyridine) immobilized copper(II) salts [150]. This material was used as a recoverable heterogeneous catalyst for a one-pot synthesis of 1,4-triazoles from terminal alkynes, alkyl halides, and sodium azide.…”
Section: Magnetic Solid-supported Catalysts For Cuaacmentioning
confidence: 99%
“…A magnetic heterogeneous copper catalyst 149 was designed, and the material was prepared by supporting copper ions by polymer-functionalized Fe 3 O 4 (Scheme 33) [102]. Therein, the 4-vinylpyridine (147) and N,N′-methylenebis(acrylamide) (MBA, 148) were added to the mixture, and this was stirred for 10 min.…”
Section: Copper Anchored On Functionalized Magnetic Nanoparticles (Mnps): Efficient and Recyclable Catalysts For Cuaac Reactionsmentioning
confidence: 99%
“…47 Additionally, the use of water as a solvent is a promising approach with regard to green chemistry. 37,38,[48][49][50][51][52] Recently, we developed two types of solid supports. One is an aminopropyl-functionalized reverse phase silica gel, which is end capped with a hydrophobic alkyl group.…”
Section: Introductionmentioning
confidence: 99%